The Impact of Climate change on Water Resources in Northern Sri Lanka: Stakeholder Perspectives - Piratheeparajah, N. (University of Sri Jayewardenepura, 2024)
Climate change is a global phenomenon affecting the entire planet, including Sri Lanka. The Northern Province of Sri Lanka is particularly vulnerable to the impacts of climate change, especially regarding water resources. Public awareness of climate change and its impact on water resources is crucial for sustainable water management practices in the study area. In this context, this study attempted to analyze public perception of the climate change impact on the water resources of Northern Sri Lanka. There are different groups of water users in the study area. They were stratified as agriculture water users, industrial water users, fishing water users and domestic and drinking water users. Accordingly, a questionnaire survey was conducted using a stratified sampling method to identify consumer perceptions, and the collected data were analyzed using the SPSS tool. 87% of the consumers believe that climate change has a significant impact on water resources, and 50% of the people expressed vulnerability of the agriculture sector to the climate change impact on water resources. Water scarcity during the yala season became a crucial threat to paddy cultivation in the study area. Other kind of water users such as industrial water users, fishing water users and drinking and domestic water users face difficulties in obtaining water resources for their needs during the SWMS and FIMS. Furthermore, drinking and domestic water users mentioned that they face water quality issues especially during July, August and September. During the southwest monsoon season, water users face difficulties in obtaining water for their domestic needs due to water scarcity. Majority of the water users know about climate change, but many of them don’t know how climate change affects their water sources. Water suppliers should implement special projects regarding climate change impacts on water resources in the study area. This will lead the water users to use water efficiently and protect the water sources sustainably.